2014
DOI: 10.1108/maj-01-2014-0986
|View full text |Cite
|
Sign up to set email alerts
|

The association between disclosure of forward-looking information and corporate governance mechanisms

Abstract: Purpose – This paper aims to witness the importance of corporate governance mechanisms and investigates the relationship between the quality of disclosure of forward-looking information in the narrative sections of annual reports and the governance mechanisms for non-financial UK companies. Design/methodology/approach – Computerized content analysis using QSR NVivo 8 is used to measure the extent of forward-looking information in the nar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
67
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(76 citation statements)
references
References 51 publications
9
67
0
Order By: Relevance
“…Being an essential "mechanism for addressing agency problems and controlling the firm's risk-taking", focus on corporate governance has been one of the responses to the financial crisis (Tarraf and Majeske, 2013). The quantity and quality of risk-related information in annual reports in relation to the corporate governance mechanisms is an area of significant research interest (Al-Najjar and Abed, 2014;Oliveira et al, 2011;Abraham and Cox, 2007;Mohd Ghazali and Weetman, 2006;Lim et al, 2007;Lajili, 2009;Solomon et al, 2000;Bonaci et al, 2012).…”
Section: Links To Corporate Governancementioning
confidence: 99%
See 1 more Smart Citation
“…Being an essential "mechanism for addressing agency problems and controlling the firm's risk-taking", focus on corporate governance has been one of the responses to the financial crisis (Tarraf and Majeske, 2013). The quantity and quality of risk-related information in annual reports in relation to the corporate governance mechanisms is an area of significant research interest (Al-Najjar and Abed, 2014;Oliveira et al, 2011;Abraham and Cox, 2007;Mohd Ghazali and Weetman, 2006;Lim et al, 2007;Lajili, 2009;Solomon et al, 2000;Bonaci et al, 2012).…”
Section: Links To Corporate Governancementioning
confidence: 99%
“…A large number of studies have investigated the impact of company size on corporate governance and disclosure (Probohudono et al, 2013;Linsley and Shrives, 2006;Beretta and Bozzolan, 2004;Amran et al, 2008;Al-Najjar and Abed, 2014). It has been argued that larger companies provide a higher volume of disclosures because of the importance of communicating effectively with a large pool of stakeholders (Amran et al, 2008).…”
Section: Company Sizementioning
confidence: 99%
“…Several studies have found a positive relationship between company size and the level of voluntary disclosures (Barako et al, 2006;Salama et al, 2012;Al-Najjar and Abed, 2014;Jizi et al, 2014;Qu et al, 2015). In respect to firm profitability, Alkhatib and Marji (2012) and Uyar and Kilic (2012) found that companies with high profits are motivated to disclose more information than those with small profits.…”
Section: Empirical Modelsmentioning
confidence: 99%
“…In respect to the relationship between the financial leverage ratio and the level of FLID, agency theory claims that highly leveraged firms have a greater contractual obligation to fulfil the information requests of long-term and short-term lenders, and therefore may offer more details to meet those needs than would a less leveraged company (Watson et al, 2002;García-Meca and Sánchez-Ballesta, 2009). The literature has reported that leverage ratio has an effect on the level of FLI disclosures (Deshmukh, 2005;Li and Zhao, 2008;O'Sullivan et al, 2008;Hussainey and Walker, 2009;Basiddiq and Hussainey, 2012;Al-Najjar and Abed, 2014).…”
Section: Empirical Modelsmentioning
confidence: 99%
“…The study of these authors also revealed that the size of the boards of directors can help a better disclosure of the strategic information. According to Al-Najjar & Abed (2014), the level of disclosure of information varies according to the size, performance, cross-listing and operating cash flow of the company. It is also related to the independence of the audit committee and the ownership structure.…”
Section: Financial Information and Corporate Governancementioning
confidence: 99%